Analysis of Road Damage Management Using the Bina Marga Method on the Access Road of Politeknik Negeri Lampung - Rizki, Sekar Dwi; Asnaning, Aniessa Rinny; Tiarto, Eko Hari; Ariyanti, Titi; Wisman, Mira (Politeknik Negeri Bengkalis, 2024)
Access roads at Politeknik Negeri Lampung (Polinela) support mobility for students, lecturers, and staff. Thequality of these roads, particularly the level of damage, is a serious concern as it disrupts accessibility for students and staff.Additionally, this condition hinders academic activities and the overall operations of the campus. Adequate and appropriaterepair efforts are necessary to ensure comfort and safety within the campus environment, thereby better supportingacademic activities.The Bina Marga Method is an approach used to assess the level of road damage. The assessment isconducted using specific established criteria, such as road classification and the severity of damage. The data collected isthen analyzed to determine the priority order for repairs and maintenance plans.The access road to Polinela Campus is 1,616.4 meters long and has an average daily traffic volume of 1,011.5 passengercar units per hour, classifying it into traffic class 4. Based on the results of the analysis, the condition rating of the PolinelaCampus road is 6, indicating that the priority order for road management is 7. Under these conditions, routine maintenanceis required. The routine maintenance needed in this case includes patching holes and resurfacing the pavement.